Investigation of Pavonia urens as Potential Biosorbent in Phytoremediation of Metal Pollutants through Complexation - Rutto, S.; Lusweti, K.; Ayabei , K.; Wetungu, M. (Africa Environmental Review Journal, 2022)
Environmental pollution involving metal ions represents a potential threat to life. This is due to different chemical wastes discharged to the environment with no or minimal treatment to reduce and decrease the harmful compounds. Several herbs have been reported for use in heavy metals removal in wastewater. This study aimed at investigating the phytochemicals present and demonstrating the possible use of Pavonia urens leaves as adsorbent material through formation of a complex with selected metals zinc, copper and nickel from aquatic environment. The plant was collected from Uasin Gishu County and air dried before crushing. The grounded powder was soaked in three organic solvents (hexane, ethyl acetate, and acetone) of increasing polarity each for 48 hours followed by filtration and drying it. The extracts were placed on silica gel columns for thin layer chromatography (TLC) separation, with visibility reagents to monitor the fractions. Five fractions obtained were labelled 1A, 2A, 3A, 4B and 5 A. The GC-Mass spectrometer (MS) gave the functional groups hydroxyl (OH), amine (-NH), and (-COOH). The ability of Pavonia urens to complex with bimetallic ions in aqueous solution was also investigated using UV-VIS spectrometry which characterized absorption frequencies. The interaction of these ions with various functional groups of the bio-sorbent surfaces was revealed by UV-VIS analysis which showed that copper ions were complexed while zinc was the least giving the order Cu2+ >Ni2+ > Zn2.The results from this study showed that P. urens is a promising alternative as an eco-friendly, low-cost bio-sorbent that can effectively complex with heavy metals in aqueous solution. The phytochemical screening showed the plant is rich in bioactive compounds such as steroids, flavonoids and terpenoids. Therefore, P urens is worth consideration for investigation in the pursuit for main compounds in drug discovery and as adsorbent.